Emerging and potential treatment options for sarcoidosis. (2nd January 2018) - Bandyopadhyay, Debabrata; Judson, Marc A.
ABSTRACT: Introduction : Sarcoidosis is a multisystem granulomatous disorder with a varied clinical presentation, range of organ involvement and natural course. For these reasons, the management of sarcoidosis can be challenging. Although corticosteroids are the mainstay of sarcoidosis therapy, they are associated with significant toxicity. Several second-line agents have been used as corticosteroid-sparing medications. Lately, newer drugs have been used or proposed for the treatment of sarcoidosis. These drugs are effective in blocking different cytokine pathways, implicated in immunopathogenesis of sarcoidosis. Areas covered : We review the commonly used medications to treat sarcoidosis including corticosteroids, corticosteroid-sparing cytotoxic drugs and role of anti TNF-α agents. Additionally, we describe recently studied novel anti-sarcoidosis agents. We also discuss the treatment of various non-granulomatous complications of sarcoidosis. Expert opinion : Although corticosteroids are the most effective anti-sarcoidosis medications, corticosteroid-sparing agents are often required for chronic cases because of corticosteroid side-effects. Future advances in the care of sarcoidosis will involve therapy of specific problematic phenotypes, treatment of non-granulomatous aspects of the disease, development of pharmacogenetics techniques and biomarkers to personalize care and further focus on quality of life issues endpoints to make treatment decisions.